Required ozone doses for removing pharmaceuticals from wastewater effluents - Antoniou, Maria G.; Hey, Gerly; Rodríguez Vega, Sergio; Spiliotopoulou, Aikaterini; Fick, Jerker; Tysklind, Mats; La Cour Jansen, Jes; Andersen, Henrik Rasmus (My University, 2013)
The aim of the this study was to investigate the ozone dosage required to remove active pharmaceutical ingredients (APIs) from biologically treated wastewater of varying quality, originated from different raw wastewater and wastewater treatment processes.Secondary effluents from six Swedish wastewater treatment plants (WWTP) were spiked with 42 APIs (nominal concentration 1μg/L) and treated with different O3 doses (0.5-12.0mg/L ozone) in bench-scale experiments.In order to compare the sensitivity of APIs in each matrix, the specific dose of ozone required to achieve reduction by one decade of each investigated API (DDO3) was determined for each effluent by fitting a first order equation to the remaining concentration of API at each applied ozone dose. Ozone dose requirements were found to vary significantly between effluents depending on their matrix characteristics.The specific ozone dose was then normalized to the dissolved organic carbon (DOC) of each effluent. The DDO3/DOC ratios were comparable for each API between the effluents.15 of the 42 investigated APIs could be classified as easily degradable (DDO3/DOC≤0.7), while 19 were moderately degradable (0.7<DDO3/DOC≤1.4), and 8 were recalcitrant towards O3-treatment (DDO3/DOC >1.4). Furthermore, we predict that a reasonable estimate of the ozone dose required to remove any of the investigated APIs may be attained by multiplying the experimental average DDO3/DOC obtained with the actual DOC of any effluent.
Keywords: Matrix effect; Ozonation; Ozone dose; Pharmaceuticals; Wastewater